0731 Bidirectional Relationships in Hawaii's College Students' Sleep. (27th April 2018) - Gilles, A A; Yepez-Haro, S C
Abstract: Introduction: Little research has examined bidirectional relationships among multiple, biopsychosocial systems that contribute to/exacerbate sleep impairment and poor health outcomes in diverse young adults. This study examined independent and moderating effects of lifestyle and health status on sleep quality and early markers of disease in a diverse sample of college students. Methods: Self-report, survey data from an on-going, study was examined. Students(N=33; mean=22.4 years) were representative of ethnic diversity in Hawaii. Sleep duration and quality, napping, total Epworth Sleepiness Scale score(ESS), academic rigor, physical/mental health, employment, sleeping environment, technology use, socioemotional support, substance use, diet, exercise, stress, medical conditions, and desire to improve sleep were measured. Kruskal-Wallis H test, one-way ANOVA, and Mann-Whitney U test were performed. Results: Students reported sleeping ≤ 6 hours on weekdays(66.7%) and weekends(48.5%), trouble falling asleep(53%), irregular sleep schedules(57.5%), difficulty staying awake(50%), napping(70%), awaken feeling tired(87.9%), substance use to aid sleep(58.24%), and desire to improve sleep(87%). Statistically significant differences in regularity of sleep schedule(χ 2 (4)=16.163, p =0.003); sleep quality(χ 2 (4)=9.503, p =0.05); feeling lonely(χ 2 (4)=11.123, p =0.025), irritable(χ 2 (4)=10.936, p =0.027), and overwhelmed(χ 2 (4)=9.644, p =0.047); exercise frequency(χ 2 (4)=15.24, p =0.004); depressant use to aid sleep(χ 2 (4)=7.911, p =0.048); diagnoses of diabetes(χ 2 (4)=8.571, p =0.036), high blood pressure(χ 2 (4)=15.0, p =0.002), or sleep disorder(χ 2 (4)=11.796, p =0.008); and health-related stress(χ 2 (4)=7.832, p =0.05) were found between frequencies of feeling tired upon waking. Statistically significant differences in BMI(χ 2 (4)=10.426, p =0.034); sleep disturbance from light(χ 2 (4)=9.584, p =0.048) and others' sleep(χ 2 (4)=10.267, p =0.036); ESS(χ 2 (4)=12.042, p =0.017); and healthful eating(χ 2 (4)=9.664, p =0.046) between prevalence of irregular sleep were found. Statistically significant difference in mean ESS between frequencies of eating fast food ( F (2, 29)=5.286, p =0.011) was reported. Daily electronic device use(46.8%;≥ 6 hours) influenced sleep (90.9% kept within reach; 84.3% used before sleeping; 50% impeded falling asleep). Students reporting difficulty falling asleep due to device use before bed were enrolled in statistically significantly more semester credits ( U =48.5, p =0.033). A statistically significant difference in mean ESS between groups who reported prevalence of irritability was reported ( F (4, 27)=6.94, p =0.001). Statistically significant differences in hopelessness(χ 2 (10)=23.762, p =0.008); future-related stress(χ 2 (10)=19.301, p =0.037); high blood pressure(χ 2 (10)=31.0, p =0.001); and ESS(χ 2 (10)=18.67, p =0.045) between different races were reported. Conclusion: College students with sleep difficulties experience bidirectional relationships of mood, academic rigor, health-related behaviors, chronic medical conditions, and future-related stress, while desiring improved sleep quality and engaging in self-medicated methods to aid sleep. Support (If Any):